STRUKTUR RUANG PERMUKIMAN SUKU ATONI BERBASI BUDAYA, STUDI KASUS: KAMPUNG ADAT TAMKESI, KABUPATEN TIMOR TENGAH UTARA (Culturally Based Living Space Structure of Antoni People Case Study of Tamkesi Indigenous Village of North Central Timor District) - Amandus Jong Tallo (Tesa Arsitektur, 2013)
ABSTRACT Since the olden days the culture of settling was realized as one of the important heritages handed down from generation to generation. In a society that firmly upheld their culture, such as Balinese, the settlement structure was determined by the cosmic system. It was concretized by the existence of the mountain as the orientation of a sacred space and the ocean as the orientation profane space. In Yogyakarla the settlement structure was determined by a person's life cycle that was described by South Ocean to Mount Merapi. One of the philosophies in determining a spatial structure was based on kinship system and sex. Atoni people arranged their settlement space based on kinship in which the spatial organization of was formed on the basis of gender or sexual difference. Atoni's settling culture could be recognized by spatial symbolism that was strongly associated with sexual dichotomy. Each cardinal direction that was associated with only one sex was not always consistent because the head of the community was called "man-woman". He was indeed a real man but he also did women's jobs. A house was specifically placed with that particular direction that was directly linked to the holding of the ceremony of the building construction. This study explained about settling space construction that was based on the culture of A toni tribe. Keywords: spatial structure, culture, Atoni. ABSTRAK Sejak dahulu dapat disadari bahwa budaya bermukim adalah salah satu warisan penting yang diturunkan secara turun-temurun. Dalam masyarakat yang memegang teguh budaya, misalnya di Bali, struktur permukiman ditentukan oleh sistem kosmis yang diwujudkan melalui gunung sebagai orientasi ruang yang sakral, dan laut sebagai orientasi ruang yang profane Pada masyarakat Jogja, struktur permukiman ditentukan oleh sirklus hidup seseorang yang digambarkan melalui laut selatan hingga gunung Merapi. Salah satu filosofi dalam mementukan struktur ruang adalah sistem kekerabatan dan jenis kelamin. Masyarakat suku Aton; juga menata ruang permukiman berdasarkan hubungan kekerabatan, dimana organisasi ruang terbentuk atas dasar jenis kelamin. Budaya bermukim orang Atoni dapat dikenal dari simbolisme spasialnya, yang sangat terkait dengan diktonomi jenis kelamin. Setiap arah kardinal dikaitkan dengan satu jenis kelamin tidak selalu sejalan, karena kepala suku disebut npria-wanita" yang memang seorang pria, tetapi melakukan pekerjaan wanita. Rumah secara khusus diletakan dengan aturan arah khusus yang langsung dikaitkan dengan penyelenggaraan upacara dalam pend irian bangunan. Melaui kajian ini dapat dilihat adanya pembentukan ruang permukiman berbasis budaya Suku Atoni. Kata Kunci: struktur ruang, budaya, Atoni.